A responsabilidade social corporativa nas Indústrias Granfino: um estudo de caso - Freitas, Carla Helena Gonçalves (2013)
This present research aims to present how the implementation is made Corporate Social Responsibility (RSC) an organization. The theme has been increasing recent decades within organizations increasingly reinforcing the role that companies should take to society, in a clear, transparent and ethical. Seeking to base this study, the theoretical framework, corporate social responsibility, presenting the practices of RSC and indicators of social responsibility. And aims to achieve the proposed objective of this work , a detailed case study Industries Granfino a family-owned company , based in Baixada Fluminense - RJ , and identified that the implementation of corporate social responsibility in Granfino been implemented with positive, instead , the ethics and values have always guided Coelho family. The work included an analysis of the balance sheets published by Granfino Industries, along with an in-depth interview with the President Mrs. Silvia Coelho Lantimant and Mr. Carlos Henrique Menditti, Director of the Center for corporate social responsibility, with a field research and a qualitative analysis, based on a literature review and a descriptive study of data and information in the reports of social reports published from 2007 to 2012.